Potential Antinociceptive Effects of Chinese Propolis and Identification on Its Active Compounds - Liping Sun; Lei Liao; Bei Wang (Journal of Immunology Research)
Propolis is an important bee product which has been applied to the treatment of several diseases. The aim of this study was to understand the material basis of Chinese propolis on pain relief; different Chinese propolis fractions (40W, 40E, 70E, and 95E raw propolis extracted followed by 40%, 70%, or 95% ethanol) were prepared, and their antinociceptive effects were evaluated. By analyzing using UPLC-Q-TOF-MS, we showed that 40W was rich in phenolic acids, like caffeic acid, while 40E, 70E, and 95E have relatively high levels in flavonoids, like galangin, pinocembrin, and chrysin. Notably, chrysin amounts in 70E and 95E are much higher than those in 40E fraction. Antinociceptive effects by these propolis fractions were evaluated in mice using acetic acid-induced writhing test, hot plate test, and tail immersion test, respectively. We noticed that only 40E fraction showed a significant reduction on acetic acid-induced writhing test. Importantly, in the hot plate test, all groups showed their effectiveness, except for the 70E group. We also noticed that 40W, 40E, and 95E administration caused an increase in the tail withdrawal latency of the mice. These data suggested that the different antinociceptive effects of different fractions from Chinese propolis extracts are directly link to their flavonoid composition.